Need Analysis for Research and Development of Automatic Sprinkling System as The Instructional Aids in Physics - Yonas Ferdinal Silaban; Ngia Masta (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
Instructional aids will made student easier to understanding and applying physics concepts. This study aims to obtain data and analyze the student’s needs toward to the instructional ais soil moisture measurement in physics lesson. Samples in study were student of 33 peoples, taken from class XH at SMAN 71 Jakarta with technique purposive sampling. This study resulted: physics learning motivation of student are in the medium category, with attention 87.88%, relevance 55.30%, confidence 60.61% and satisfaction 87.12%. Curriculum analysis show in class X, measurement lesson still can be developed to soil moisture measurement based on contextual learning approach. Based on style learning, 4,48% students who have visual learning style, auditory 24.24% and kinesthetic 27.27%. A total of 59.85% students experience difficulty in learning physics. As many as 79.55% of students agree that hands on method in learning can reduce difficulty in learning physics. As many as 87.12% of students agree that they need automated instrument in physics practice and only 39.39% of students has known about Arduino. The frequently used learning media in class were on audio-visual category, starting from power point slide presentation, Canva’s slides presentation, video, simulation and animation. All of those findings were supported research and development of oto-sprinkler system by using humidity sensor and Arduino Uno. Result of this study will become the base contextual in developing contextual teaching aids in form of soil moisture measurement, so that can increase the physics learning motivation in student.